St. Louis eco-boulevard - Bryan, Megan (Kansas State University, 2010)
Cities and nature are often popularly viewed as polar opposites. Many American cities are seen as “destructive of nature, gray and natureless, distinct and separate from natural systems” (Beatley 2008, 189). Cities lacking in ecological functions can benefit from the application of Green Urbanism theory. Green Urbanism incorporates ecological features as central design elements, cities, and to restore, nurture, and celebrate urban ecology. Unique ecological features can affect a place in positive ways while adding and establishing an identity for the city. One city that has been stuck in a gray and natureless state is St. Louis, Missouri, in particular, the Central business district. In order to transform St. Louis into a more ecologically rich city, an eco-boulevard will be implemented. An eco-boulevard is a green ribbon that collects stormwater runoff and connects people to surrounding local amenities. In addition to stormwater benefits, the eco-boulevard will serve as a visual and physical connector for pedestrians to public destinations, and connect pedestrians with other pedestrians by serving as its own destination. The eco-boulevard can also provide multiple ecological and social benefits to promote healthy places with a high quality of life. In order to achieve the implementation of an eco-boulevard, a thorough analysis of watersheds, key low points, transportation hubs, public destinations, and established pedestrian traffic routes were considered. The design of the eco-boulevard is concentrated in areas where low points in elevation, transportation hubs, public destinations, and highly traveled pedestrian traffic routes converge. At the intersection of these elements, unique features capture and store stormwater runoff. As a whole, the entire eco-boulevard improves urban ecology through the use of vegetation, street trees, and the recycling of water.
Keywords: Eco-boulevard; Stormwater management; Urban design; St. Louis, Missouri; Landscape architecture; Landscape Architecture (0390)